2022
DOI: 10.1021/acs.macromol.2c01140
|View full text |Cite
|
Sign up to set email alerts
|

Fully Degradable Polyacrylate Networks from Conventional Radical Polymerization Enabled by Thionolactone Addition

Abstract: We report the preparation of degradable polymer networks by conventional free radical copolymerization of n-butyl acrylate with a crosslinker (1 mol %) and dibenzo[c,e]oxepane-5thione (DOT) as a strand-cleaving comonomer. Addition of only 4 mol % of DOT imparts the synthesized networks with full degradability by aminolysis, whereas gels with less DOT (2−3 mol %) cannot be degraded. This data confirms the recently proposed reverse gel-point model for networks prepared by free radical polymerization and demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Given that all above ATRPs proceeded in the presence of lactone, we investigated whether its presence led to chain transfer. A recent study concluded that chain transfer to the lactone was not significant during free radical polymerization . In agreement, we found that the addition of up to 20 mol % of lactone ( 2 ) to ATRPs of PEGA in toluene did not cause a observable chain transfer, see Figure S1.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Given that all above ATRPs proceeded in the presence of lactone, we investigated whether its presence led to chain transfer. A recent study concluded that chain transfer to the lactone was not significant during free radical polymerization . In agreement, we found that the addition of up to 20 mol % of lactone ( 2 ) to ATRPs of PEGA in toluene did not cause a observable chain transfer, see Figure S1.…”
Section: Resultssupporting
confidence: 90%
“…Despite the ability to make degradable copolymers with narrow size distributions, the seemingly unpreventable loss of typically 50% of the DOT feed and the inability to form polymers from formulations containing more than 15 mol % of DOT meant that it was not possible to make copolymers containing more than ∼7 mol % DOT through the above methods. Although copolymers with lower DOT content have been shown to be useful (e.g.,, fully degradable networks), ,, we sought to increase the DOT content of ATRP-made copolymers. In a typical copolymerization, approximately 25 μmol of DOT were converted to lactone.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal stability of polymethacrylate 5 was the lowest among them, most likely because of the generation of vinylidene chain-end formed via a disproportionation reaction and the depolymerization of the main chain. The T d5 values of polyacrylate 4 and polymethacrylate 5 were much higher than those of commercially available poly­(butyl acrylate) (poly­(BA)), poly­(methyl methacrylate) (poly­(MMA)), and poly­(2-hydroxyethyl methacrylate) (poly­(HEMA), clearly demonstrating that the incorporated macrocyclic units into the main chain are effective in the enhancement of thermal stability (entries 2 vs 12 and entries 6 vs 13 & 14). The lower T d5 value of polyacrylate 6 than that of poly­(BA) clarifies that thermal decomposition of the urethane bonds in the side chains is faster than that of the main chain (entries 9 vs 12).…”
Section: Resultsmentioning
confidence: 96%
“…Among them, copolymerization of heteroatom‐containing cyclic monomers with common vinyl monomers, by which labile carbon‐heteroatom bonds can be introduced via ring opening of the cyclic structures, is one of the most efficient methods [23–26] . Various cyclic compounds, which are copolymerizable via ring‐opening reactions, have been developed to date and include cyclic ketene acetals, [27–40] thionolactones, [41–47] and cyclic allylic sulfur compounds [48–52] for radical polymerization as well as oxiranes, [53, 54] cyclic acetals, [55, 56] hemiacetal esters, [57] and 1,3‐dioxa‐2‐silacycloalkanes [58] for cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Among them, copolymerization of heteroatom-containing cyclic monomers with common vinyl monomers, by which labile carbon-heteroatom bonds can be introduced via ring opening of the cyclic structures, is one of the most efficient methods. [23][24][25][26] Various cyclic compounds, which are copolymerizable via ring-opening reactions, have been developed to date and include cyclic ketene acetals, [27][28][29][30][31][32][33][34][35][36][37][38][39][40] thionolactones, [41][42][43][44][45][46][47] and cyclic allylic sulfur compounds [48][49][50][51][52] for radical polymerization as well as oxiranes,…”
Section: Introductionmentioning
confidence: 99%